Rancang Bangun Hotspot pada Perusahaan Jingga Enterprise - Dian Gustina; Achmad Sumbaryadi (Fakultas Ilmu Komputer dan Desain - Unsurya, 2016)
The need for information is very important today as the progress and development of information technology that increasingly sophisticated with the increasingly rapid development. To help get that information quickly, accurately and precisely, the technology creates a wireless area network or commonly called by the people called hotspot. Such information can be accessed in places that already have a wireless area network. We do not have to laboriously search for internet cafes to access the Internet. With this technology we can get the information anywhere through notebooks, PDAs, mobile phones and other devices that can connect to wireless networks The author in making hotspot companies doing JINGGA ENTERPRISE installation and the installation Wireless Area Network (HotSpot). Processes include software and hardware support from Wirelless network.